Ukuran kranial dan indeks sefalik pada anak retardasi mental (Cranial size and cephalic index of mentally retarded children) - Dewi Elianora; Iwa Sutardjo; Bambang Udji Rianto (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Mental retardation is imperfect condition of mental development which resulted in delay of motoric development, speech and in adaption with the environment. The common symptoms is brain growth disorder, which affects the cranial size and the intelectual function lower than average (<70). Purpose: This study was aimed to determine the difference of cranial size and cephalic index of mentally retarded children compared with normal chilren based on antropometry and cephalometric measurement. Methods: This research was epidemiology analytic observational with case control design. The cranial size and cephalic index measurements were carried out on 168 children in range of age 7-12 years old (84 were moderate mental retarded children and 84 were normal children). Data was statistically analyzed with t-test. Results: The size of cranial and cephalic on index on mentally retarded children were smaller than normal children. S-N and G-Op size were shorter than normal children, the results of S-N differences (-4.4), S-Ar (-2.38) and G-Op (-5.5), Eu-Eu (-8.24). The results analysis of linear and angle component cranial base (S-N, S-Ar and <NSAr) was significantly smaller than normal children. Based on age and genders, and the normal child was normocephalic. Odds ratio value of the head profile based on age groups 2.10 times (CI 0.290-3.390) compared to normal children 0.99 (CI 0.025-0.375). Based on gender the odds ratio value 1.469 times (CI 0.429-5.035) compared normal child 0.562 (CI 0.19-1.65). The head length and cranial base had related with gender. Cranial size on boys were bigger than girls. Conclusion: It is concluded that the cephalic index and the size of cranial base of mentally retarded children were smaller than normal children.Latar belakang: Retardasi mental merupakan ketidaksempurnaan perkembangan mental yang mengakibatkan keterlambatan perkembangan motorik, bicara dan penyesuaian diri dengan lingkungan. Gejala umum adalah gangguan pertumbuhan otak yang berpengaruh terhadap ukuran kranial dan fungsi intelektual (Quetient Intelegence) rendah (kurang dari 70). Tujuan: Penelitian ini bertujuan mengukur perbedaan ukuran kranial dan indeks cephalik anak retardasi mental umur 7-12 tahun dibandingkan anak normal berdasarkan pengukuran antropometri dan sefalometri. Metode: Penelitian epidemiologi analitik observasional dengan rancang penelitian case control. Pengukuran ukuran kepala dan indeks sefalik dilakukan pada 168 anak umur 7-12 tahun (84 anak retardasi mental sedang dan 84 anak normal). Data dianalisis dengan uji-t. Hasil: Ukuran kranial dan indeks sefalik anak retardasi mental lebih kecil, terlihat dari ukuran S-N dan G-Op lebih pendek pada anak retardasi mental dibanding anak normal. Rerata selisih perbedaan -4.4 (S-N), -2.38 (S-Ar) dan G-Op (-5.05 mm), Eu-Eu (-8.24). Hasil komponen garis dan sudut ukuran basis kranium (S-N, S-Ar dan sudut N-S-Ar) lebih pendek secara bermakna pada anak retardasi mental dibanding anak normal. Berdasarkan kelompok umur dan jenis kelamin pada anak retardasi mental lebih banyak ditemukan bentuk kepala brakisefalik, dan anak normal normosefalik. Nilai odds ratio bentuk kepala berdasarkan kelompok umur 2.10 kali (95% CI 0.025-0.375) dibanding anak normal 0.99 (CI 0.290-3.390). Berdasarkan jenis kelamin nilai odds ratio 1.469 kali (CI 0.429-5.035) dibanding normal 0.562 (CI 0.19-1.65). Panjang kepala dan basis kranial ada kaitannya dengan jenis kelamin, anak laki-laki ukuran kranialnya lebih besar dari anak perempuan. Simpulan: Ukuran kepala dan basis kranial anak retardasi mental lebih kecil dari anak normal.